Determinan Struktur Modal Perusahaan yang Terdaftar di JII70 - Syahfitri Suryaningsi Welkom; Anggun Pratiwi; Ditha Riyansa; Allysa Azzarah Welkom (Universitas Negeri Padang, 2024)
Capital structure policy is a core financing decision for a company that affects company value. Companies need to be careful in determining where the source of financing comes from, whether from debt or equity sourced from their own funds or from the issuance of shares. Wrong capital structure policies can lead a company into financial distress and bankruptcy. Over the last five years, more and more companies have obtained financing through the issuance of shares on the sharia stock market. The number of investors investing their funds in this market has also increased. Based on this, the aim of this research is to find out and understand what the factors of company characteristic that effect the capital structure in companies listed on the Jakarta Islamic Index 70 (JII70) during the 2018-2022 period. This study uses a quantitative approach. The model used is dynamic panel data regression with the System-GMM as the analysis method. The data used is secondary data for the 2018-2022 period which comes from company financial reports collected through IDX (Indonesia Stock Exchange). The population in this study were 70 companies registered on JII70. The sampling method was purposive sampling. The number of samples selected was 29 companies. The results of hypothesis testing show that the factors of company characteristic that effect the capital structure are return on equity, profit margin, current ratio, and total asset turnover.